Pharyngeal flap using carotid artery mobilization in 22q11.2 deletion syndrome with velopharyngeal insufficiency. (May 2019) - Greenberg, Max; Caloway, Christen; Hersh, Cheryl; Ryan, Daniel; Goldenberg, Paula; Hartnick, Christopher
Abstract: Introduction: 22q11.2 deletion syndrome is the most common microdeletion syndrome in children. Many patients with this disease develop craniofacial defects including cleft palate, bifid uvula, and velopharyngeal insufficiency. Our study adds to the current body of literature by describing a novel technique of carotid mobilization performed in conjunction with pharyngeal flap surgery in patients with extensive medialization of the carotid artery. Methods: Carotid artery mobilization followed by insertion of a superiorly based pharyngeal flap was performed on two patients, a 10-year-old girl and a 5-year-old boy, with 22q11.2 deletion syndrome concurrent with velopharyngeal insufficiency. Results: Neither patient experienced significant post-operative issues. Following the procedure, parents of both patients noted significant speech and voice improvement. Both patients had improvements in VPI Effects On Life Outcome (VELO) scores, nasometry, and production of paragraph passages following surgery. Conclusions: Our study describes a novel surgical treatment for children with 22q11.2 deletion syndrome with significant velopharyngeal insufficiency (VPI). The procedure wherein is characterized by an extensive mobilization of the carotid artery followed by implantation of a pharyngeal flap. This technique resulted in no significant intra-operative bleeding, and was measured to be successful as noted by nasometry scores and changes in pre- and post-op VELO scores.